Clinician-reported barriers to using exposure with response prevention in the treatment of paediatric obsessive-compulsive disorder - Keleher, Julia (J Obsessive Compuls Relat Disord, 2020)
Exposure techniques are underutilised in the treatment of anxiety disorders in routine practice, but little is known about the use of exposure with response prevention (ERP) for OCD, particularly in youth. The current study aimed to examine the utilisation of ERP for paediatric OCD via an anonymous online survey completed by clinicians (N = 107). Specifically, we explored the association of clinician characteristics and OCD symptom subtypes with ERP use, as well as clinician-reported barriers to ERP implementation. The majority of clinicians reported commonly using ERP when treating youth with OCD, and rates of ERP use were highest among clinical psychologists. Clinician-held negative beliefs about exposure were significantly associated with lower ERP use. Additionally, clinicians reported being less likely to use ERP to treat hoarding symptoms and taboo obsessions, compared to other OCD symptom subtypes. The most commonly endorsed barriers to successful ERP implementation were aspects of the phenomenology of OCD (e.g. covert compulsions, frequently changing rituals) as opposed to general barriers (e.g. insufficient time during sessions). Overall, our findings suggest that OCD presents unique challenges for clinicians delivering exposure-based therapy. Training should address these OCD-specific obstacles in order to promote dissemination of ERP for youth with OCD.